2020
DOI: 10.1029/2019jb019315
|View full text |Cite
|
Sign up to set email alerts
|

The Lithospheric Thickness Control on the Compositional Variation of Continental Intraplate Basalts: A Demonstration Using the Cenozoic Basalts and Clinopyroxene Megacrysts From Eastern China

Abstract: Studies on intraplate ocean island basalts have demonstrated the control of lithosphere thickness on the extent of melting and pressure of melt extraction (i.e., the lid effect). However, whether lithosphere thickness also controls the composition of within‐continent basalts remains unclear. Here, we test this hypothesis by studying the Cenozoic basalts contaitning clinopyroxene megacrysts from 10 localities throughout eastern continental China with a north‐south spatial coverage in excess of 2,500 km. Indeed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 116 publications
4
15
0
Order By: Relevance
“…A fertile mantle source has higher SiO 2 , Al 2 O 3 , FeO T , and TiO 2 contents and lower MgO content than less-fertile mantle [48,49]. Melt SiO 2 and Al 2 O 3 contents increase and FeO and MgO contents decrease with decreasing melting pressure [37]. Previous studies have suggested that the mantle source of Pohnpei Island is relatively homogenous [10,13], and the variations of FeO T and TiO 2 with MgO (Figure 4b,d), and SiO 2 and Al 2 O 3 with FeO T (not shown) thus reflect the effect of melt extraction pressures rather than mantle composition.…”
Section: Primary Magma Composition and Mantle Melting Processmentioning
confidence: 98%
See 4 more Smart Citations
“…A fertile mantle source has higher SiO 2 , Al 2 O 3 , FeO T , and TiO 2 contents and lower MgO content than less-fertile mantle [48,49]. Melt SiO 2 and Al 2 O 3 contents increase and FeO and MgO contents decrease with decreasing melting pressure [37]. Previous studies have suggested that the mantle source of Pohnpei Island is relatively homogenous [10,13], and the variations of FeO T and TiO 2 with MgO (Figure 4b,d), and SiO 2 and Al 2 O 3 with FeO T (not shown) thus reflect the effect of melt extraction pressures rather than mantle composition.…”
Section: Primary Magma Composition and Mantle Melting Processmentioning
confidence: 98%
“…Major-element data from previous studies are included for comparison [9,10,18]. Compositional trends [37] of melts derived from less to more fertile mantle (green arrows) and from high to low pressures of melt extraction (purple arrows) are shown in (a-d). [32], are included.…”
Section: Major Elementsmentioning
confidence: 99%
See 3 more Smart Citations